2002
DOI: 10.1177/09680519020080061001
|View full text |Cite
|
Sign up to set email alerts
|

Direct hemoperfusion with polymyxin B-immobilized fiber improves shock and hypoxemia during endotoxemia in anesthetized sheep

Abstract: This study evaluates the effect of direct hemoperfusion (DHP) using polymyxin B-immobilized fibers (PMX-F) as an extracorporeal blood filter on systemic hypotension and lung injury during endotoxemia Sheep were anesthetized, intubated, mechanically ventilated with 50% oxygen and connected to the DHP system between the right femoral artery and left jugular vein. Group 1 (n = 6)sheep were infused with 10 microg/kg Escherichia coli endotoxin over a 30 min period. At the same time, sheep underwent DHP with PMX-F (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 37 publications
1
14
1
Order By: Relevance
“…Acute exacerbations of IPF have been described high mortality in several reports (4,5,7,18 (10). In an animal model of sepsis, PMX has been reported to improve oxygenation through suppression of nitric oxide production (19 (8). Additionally, PMX treatment once or twice for 4 hours has reportedly improved the survival of sepsis patients (13).…”
Section: Discussionmentioning
confidence: 99%
“…Acute exacerbations of IPF have been described high mortality in several reports (4,5,7,18 (10). In an animal model of sepsis, PMX has been reported to improve oxygenation through suppression of nitric oxide production (19 (8). Additionally, PMX treatment once or twice for 4 hours has reportedly improved the survival of sepsis patients (13).…”
Section: Discussionmentioning
confidence: 99%
“…Aoki et al [11] suggested that the reduction of endotoxin concentration by PMX might reduce pulmonary vasoconstriction and intrapulmonary shunting and increase the arterial oxygen tension (PaO 2 )/inspiratory oxygen fraction (FiO 2 ) (P/F) ratio in sepsis and septic shock. Yamamoto et al [22] showed that PMX significantly decreased intrapulmonary shunt and improved deteriorated oxygenation during endotoxemia in anesthetized sheep. However, since in the present study blood endotoxin levels in IP patients with acute exacerbation were all below the level of detection ( !…”
Section: Discussionmentioning
confidence: 99%
“…However, PMX is effective against both gram-negative and gram-positive sepsis (17 (15). In an animal model of sepsis, PMX improves oxygenation through the suppression of nitric oxide production (21). Kushi (26).…”
Section: F I G U R E 5 T H E C H E S T I Ma G E S O F T H E P a T Imentioning
confidence: 99%